Regional Variation in the Incidence and Outcomes of In-Hospital Cardiac Arrest in the United States. Issue 16 (21st April 2015) - Kolte, Dhaval; Khera, Sahil; Aronow, Wilbert S.; Palaniswamy, Chandrasekar; Mujib, Marjan; Ahn, Chul; Iwai, Sei; Jain, Diwakar; Sule, Sachin; Ahmed, Ali; Cooper, Howard A.; Frishman, William H.; et al.
<x xml:space="preserve">Abstract</x> Background— Regional variation in the incidence and outcomes of in-hospital cardiac arrest (IHCA) is not well studied and may have important health and policy implications. Methods and Results— We used the 2003 to 2011 Nationwide Inpatient Sample databases to identify patients ≥18 years of age who underwent cardiopulmonary resuscitation (International Classification of Diseases, Ninth Edition, Clinical Modification procedure codes 99.60 and 99.63) for IHCA. Regional differences in IHCA incidence, survival to hospital discharge, and resource use (total hospital cost and discharge disposition among survivors) were analyzed. Of 838 465 patients with IHCA, 162 270 (19.4%) were in the Northeast, 159 581 (19.0%) were in the Midwest, 316 201 (37.7%) were in the South, and 200 413 (23.9%) were in the West. Overall IHCA incidence in the United States was 2.85 per 1000 hospital admissions. IHCA incidence was lowest in the Midwest and highest in the West (2.33 and 3.73 per 1000 hospital admissions, respectively). Compared with the Northeast, risk-adjusted survival to discharge was significantly higher in the Midwest (odds ratio, 1.33; 95% confidence interval, 1.31–1.36), South (odds ratio, 1.21; 95% confidence interval, 1.19–1.23), and West (odds ratio, 1.25; 95% confidence interval, 1.23–1.27). IHCA survival increased significantly from 2003 to 2011 in the United States and in all regions (all Ptrend<0.001). Total hospital cost was highest in the West, whereas discharge to skilled nursing facility and use of home health care among survivors was highest in the Northeast. Conclusions— We observed significant regional variation in IHCA incidence, survival, and resource use in the United States. This variation was explained only partially by differences in patient and hospital characteristics. Further studies are needed to identify other potential factors responsible for these regional differences to improve outcomes after IHCA.